2018
DOI: 10.2147/opth.s172894
|View full text |Cite
|
Sign up to set email alerts
|

Uncorrected visual acuity, postoperative astigmatism, and dry eye symptoms are major determinants of patient satisfaction: a comparative, real-life study of femtosecond laser in situ keratomileusis and small incision lenticule extraction for myopia

Abstract: PurposeTo compare factors affecting patient satisfaction after femtosecond laser in situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE) for myopia in the real-life situation study.MethodsThe SMILE group included 100 eyes (51 patients) and the FS-LASIK group 200 eyes (102 patients). In addition to clinical examination, dry eye symptoms and patient satisfaction with far and near vision were reported and graded on the visual analog scale preoperatively and one month after the operation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Again, no statistically significant differences in CDVA were found between the two procedures at 3 months postoperatively, and the mean safety and efficacy indices for those in the SMILE group (1.1060.14; 1.0260.17) were similar to those in the LASIK group (1.1260.15; 1.0760.20) as well [10]. The study found that the refractive error was within ± 0.5 D of target refraction in 93% of treated eyes in both groups 3 months after surgery [10], in agreement with the findings of other studies comparing the two procedures, which demonstrated high refractive accuracy and clinical efficacy for both treatments [1113]. Furthermore, the two techniques were found to be equally safe, as no patient had a loss of more than two lines of best-corrected visual acuity (BCVA) throughout the 6-month follow-up period or suffered from significant postoperative complications such as epithelial defect, lamellar keratitis or epithelial implantation.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Again, no statistically significant differences in CDVA were found between the two procedures at 3 months postoperatively, and the mean safety and efficacy indices for those in the SMILE group (1.1060.14; 1.0260.17) were similar to those in the LASIK group (1.1260.15; 1.0760.20) as well [10]. The study found that the refractive error was within ± 0.5 D of target refraction in 93% of treated eyes in both groups 3 months after surgery [10], in agreement with the findings of other studies comparing the two procedures, which demonstrated high refractive accuracy and clinical efficacy for both treatments [1113]. Furthermore, the two techniques were found to be equally safe, as no patient had a loss of more than two lines of best-corrected visual acuity (BCVA) throughout the 6-month follow-up period or suffered from significant postoperative complications such as epithelial defect, lamellar keratitis or epithelial implantation.…”
Section: Resultssupporting
confidence: 87%
“…In terms of surgically induced astigmatism (SIA), one study in India including 30 eyes with low to moderate myopic astigmatism reported that there was no statistically significant difference between the two techniques (LASIK: 1.21 ± 0.85; SMILE: 1.02 ± 0.43; P > 0.05) [19]. However, a study in Finland found that the SMILE group (100 eyes with preoperative SE ranging from −1.38 to −8.25 D) had more postoperative astigmatism than the FS-LASIK-treated group (200 eyes with preoperative SE ranging from −0.63 to −11.63 D) [11]. Thus the results are inconclusive with regard to which technique is more likely to induce astigmatism, and additional evidence from prospective studies and randomized controlled trials is needed.…”
Section: Resultsmentioning
confidence: 99%
“…This study appears to highlight that SMILE surgery is safe to perform in patients with a low FTBUT. This is supported by a previous which suggests that SMILE surgery can result in a decrease in dry eye symptoms postoperatively [ 26 ].…”
Section: Discussionsupporting
confidence: 76%
“…In our previous studies, we compared FS-LASIK and SMILE for myopic treatment 38. In the comparison, myopic patients treated with FS-LASIK had no change in self-reported dry eye symptoms, but patients treated with SMILE reported fewer dry eye symptoms after 1-month follow-up than preoperatively.…”
Section: Discussionmentioning
confidence: 99%